Urban regional resilience: How do cities and regions deal with change? - (:unkn) unknown (Springer, 2011)
Die Beiträge kreisen um den ursprünglich aus der Psychologie stammenden und in die Disziplinen der Raumforschung und Regionalwissenschaft übernommenen Begriff der Resilienz in der Bedeutung von Störungstoleranz oder Widerstandsfähigkeit gegenüber Prozessen des Wandels. In den Berichten aus der Forschungstätigkeit der beteiligten Institute und einer Reihe von Kurzbeiträgen geht es um die theoretische Einordnung des Resilienzbegriffs und um die Frage, warum manche Städte und Regionen resilienter gegenüber Herausforderungen wie Klimawandel, Wirtschaftskrisen oder dem demographische Wandel sind als andere. Ferner geht es um staatliche Programme, die sich den neuen Herausforderungen an die Stadt- und Regionalentwicklung stellen (Stichworte: Ressourcen-, Energieeffizienz; Stadtumbau durch demographischen Wandel, Strukturwandel der Wirtschaft) und die Rolle des Sozialkapitals in der "Neuen Regionalpolitik".

Resilience is increasingly becoming a catchword in current discussions about urban and regional development. While there has been a strong research focus on sustainability, there is a lack of understanding of the processes and factors that make cities and regions more vulnerable and others more resilient, for example, when dealing with climate change, demographic decline and ageing, as well as economic crises. The German Annual of Spatial Research and Policy 2010 sheds some light on this by discussing examples of how actors deal with change. On the one hand, concepts are described and analysed which are oriented towards increasing urban regional resilience, for example regarding energy consumption, climate change, and urban decline. Moreover, institutional aspects are discussed. On the other hand, barriers for using the concept of resilience in planning are described and suggestions are made about how to deal with these barriers in strategic planning.
Keywords: Raumordnung; Raumforschung; Raumwissenschaft; Stadt; Region; Raumstruktur; Sozialwandel; Regionalpolitik; Resilienz; Klimawandel; Anpassungsstrategie